2017
DOI: 10.3171/2015.12.jns152341
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hemorrhage associated with external ventricular drain placement and removal

Abstract: OBJECTIVE External ventricular drains (EVDs) have an important role in the management of neurological disease, and their placement is a frequently performed neurosurgical procedure. Hemorrhage is a common complication of EVD placement and occurs more frequently than originally believed. There is also risk of hemorrhage with removal of an EVD, which has not been well described. The authors investigated the risk factors associated with placement and removal of EVDs at their institution. METHODS A database was cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 30 publications
0
31
2
1
Order By: Relevance
“…In the current study, we failed to detect differences in the occurrence of postoperative hematoma in the two groups, and the frequency was also considerably lower than previous reports [6,9,17,18,[21][22][23]. Studies have previously reported rates of close to non-existent to approximately 40% [9,17,22].…”
Section: Discussioncontrasting
confidence: 96%
“…In the current study, we failed to detect differences in the occurrence of postoperative hematoma in the two groups, and the frequency was also considerably lower than previous reports [6,9,17,18,[21][22][23]. Studies have previously reported rates of close to non-existent to approximately 40% [9,17,22].…”
Section: Discussioncontrasting
confidence: 96%
“…In the current literature, the rate of hemorrhagic complications after EVD insertion ranged from 0% to 15%. [2][3][4][5] However, none of these studies reported an EVD-related mortality. We observed an overall complication rate of 2% for nICVH, which is at the lower end compared with the data published.…”
Section: Discussionmentioning
confidence: 99%
“…1 Typical complications after insertion of an EVD are the occurrence of a new intracerebral or intraventricular hemorrhage (nICVH), infection, and malpositioning of the catheter. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The optimal position of the EVD is the frontal horn of the lateral ventricle, with its tip close to the foramen of Monro.…”
Section: Introductionmentioning
confidence: 99%
“…In this series, decreased platelet levels on admission and an increasing number of EVD placement attempts correlated with an increased risk of hemorrhage. 43 Similarly, Gardner et al found that 41% of 188 EVDs placed resulted in evidence of hemorrhage on postplacement CT images, of which 20 patients had hemorrhages > 15 ml and 1 patient required evacuation of a subdural hematoma. 21 In contrast, other analyses have reported post-EVD-placement hemorrhage rates of 1%-8%, with clinically significant or symptomatic hemorrhages occurring in < 1% of patients.…”
Section: Postprocedural Hemorrhagementioning
confidence: 95%